Preventing environmental disasters: Market-based vs. command-and-control policies - Francesco Lamperti; Mauro Napoletano; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
The paper compares the effects of market-based and command-and-control climate policies on the direction of technical change and the prevention of environmental disasters. Drawing on the model proposed in Acemoglu et al. (2012, American Economic Review), we show that market-based policies (carbon taxes and subsidies towards clean sectors) exhibit bounded window of opportunities: delays in their implementation make them completely ineffective both in redirecting technical change and in avoiding environmental catastrophes. On the contrary, we find that command-and-control interventions guarantee policy effectiveness irrespectively on the timing of their introduction. As command-and-control policies are always able to direct technical change toward "green" technologies and to prevent climate disasters, they constitute a valuable alternative to market-based interventions.
Keywords: O33; O44; Q30; Q54; Q56; Q58; 330; Environmental Policy; Command and Control; Carbon Taxes; Disasters